Rotated quadrilateral dipole UWB antenna for wireless communication - Brar R.S.; Singhal S.; Singh A.K. (My University, 2025)
A double printed rotated quadrilateral dipole UWB antenna for wireless communication is presented. The rotation of quadrilateral and modification of integrated balun structure is employed to enhance bandwidth and impedance matching. The proposed antenna shows impedance bandwidth of 3.8-18.1 GHz which covers the entire C, X and Ku bands. The radiation patterns of the designed antenna structure are relatively stable and omnidirectional over the entire obtained bandwidth with an average gain of 3.6 dB. A good agreement is found between the simulated and experimental results. The proposed antenna has a simple design, comparatively compact size and more bandwidth than previous reported double rhombus antenna. © 2016, Electromagnetics Academy. All rights reserved.